2019
DOI: 10.1111/micc.12547
|View full text |Cite
|
Sign up to set email alerts
|

Application of microscale culture technologies for studying lymphatic vessel biology

Abstract: Immense progress in microscale engineering technologies has significantly expanded the capabilities of in vitro cell culture systems for reconstituting physiological microenvironments that are mediated by biomolecular gradients, fluid transport, and mechanical forces. Here, we examine the innovative approaches based on microfabricated vessels for studying lymphatic biology. To help understand the necessary design requirements for microfluidic models, we first summarize lymphatic vessel structure and function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 179 publications
(371 reference statements)
1
17
0
Order By: Relevance
“…[87] Together with the hydraulic conductivity, which is a coefficient that represents the permeability of blood vessels, the Starling Forces determine the rate of transendothelial fluid filtration. [88] Jain and colleagues reported that colloid osmotic pressures in tumors are unusually high. [89] Recent studies have revealed that osmotic stress can influence cancer cell migration, [90] cell volume, [91] cell adhesion, [92] and cell cytoskeleton structure among other cellular processes.…”
Section: Hydrostatic and Osmotic Pressurementioning
confidence: 99%
“…[87] Together with the hydraulic conductivity, which is a coefficient that represents the permeability of blood vessels, the Starling Forces determine the rate of transendothelial fluid filtration. [88] Jain and colleagues reported that colloid osmotic pressures in tumors are unusually high. [89] Recent studies have revealed that osmotic stress can influence cancer cell migration, [90] cell volume, [91] cell adhesion, [92] and cell cytoskeleton structure among other cellular processes.…”
Section: Hydrostatic and Osmotic Pressurementioning
confidence: 99%
“…Small nanoplastics were found to directly absorb through the intestinal wall of mussels [20] and bioaccumulate in barnacles [23]. Evidence of plastic particles in the terrestrial environment confirm nanoplastic uptake by plants, earthworms, and in air pollution or aerosolized particulate matter [24].…”
Section: Toxicitymentioning
confidence: 99%
“…However, studies implementing microfluidic systems to generate lymphatic vasculature are exceedingly scarce. Apart from simple monolayer systems that lack anatomical resemblance, fewer than a dozen published works have attempted to recreate the native lymphatic vasculature on-chip [14][15][16]. Most of these studies implement a single lymphatic capillary on-chip system to study solute permeability, and paracrine signaling/conditioning between lymphatic and fibroblast/tumor cells [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%